Geospatial analysis to identify promising car parks for installing electric vehicle charge points: An Oxford case study. (May 2022) - Collett, Katherine A.; Bhagavathy, Sivapriya Mothilal; McCulloch, Malcolm D.
Abstract: Historically in the UK, uptake of electric vehicles (EVs) has been dominated by those with off-street parking. In fact, a recent report by Deloitte found that nearly 90% of EV drivers currently charge privately. However, if we wish to meet the UK Government's targets of net zero by 2050 and no further sales of fully internal combustion engine vehicles after 2030, EV charging will need to be made accessible to those without driveways. Local Authorities and the companies they work with have a significant role to play in infrastructure planning to get ahead of the curve of accelerating EV uptake. This Visualising Transport Geography article investigates whether it is possible to identify locations for public EV chargers which may be more valuable to residents.